Gods and heroes from Viking mythology - Branston, Brian, 1914-.; Caselli, Giovanni, 1939- (New York : Peter Bedrick Books, 1994)
A collection of myths about Thor, Balder, King Gylfi, and other Nordic gods and goddesses.
Includes index.
Originally published: London : P. Lowe, 1978.
Keywords: Mythology, Norse -- Juvenile literature; Mythology, Norse